Ceramic Panel for Sound Insulation Application - Wan Aiman Hakim Wan Maliki; Muhd Hafeez Zainulabidin (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2020)
In order to reduce noise nowadays, many researcher find different way to solve this problem. One of the ways to reduce noise is by using a sound insulation. This research has been conducted in order to produce high density sound insulation panel made from ceramic. The fabrication of ceramic panel undergo several processes which are milling, mixing, forming, drying and sintering process. The ceramic panel of different types of forming were developed as square plate 110mm x 110 mm with a constant thickness of 5 mm. Type of forming were used for this particular study are slip casting and uniaxial press. The composition used were 100 % clay and 90% + 10 % clay cement. The transmission loss were determined by using acoustic insulation test. The apparatus consists of sound level meter, portable speaker and computer. The Sound Pressure Levels (SPL) were taken at 250 Hz, 500 Hz, 1000 Hz, 2000 Hz and 4000 Hz which based on 1 octave frequency bands. The analysis shown that the sample 90 % + 10 % clay cement casting has the higher transmission loss in the lower frequency region, the sample 90 % + 10 % clay cement uniaxial press has the higher transmission loss in the middle frequency region and lastly the sample 100 % clay uniaxial press has the higher transmission loss in higher frequency region. The sample also were tested using Charpy impact test in order to gain their impact energy and impact strength. The tests were according to ASTM-D256. Charpy impact test can determines the amount of energy absorbed by a material during fracture. The analysis shown that the impact energy of the ceramic panel have a small percentage different. It can be concluded that uniaxial press is better than the slip casting in forming ceramic insulation panel.